ANALYSIS OF EXISTENCE OF SOLUTIONS OF THE CAUCHY PROBLEM FOR DIFFERENTIAL EQUATIONS WITH FRACTIONAL DERIVATIVES - E. A. Barkova (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The Cauchy problem for differential equations with Caputo fractional derivatives is given. New methods for studying the regions of existence of solutions of these equations are presented. Analysis of changes in these areas was done by changing the settings right and left sides of the equation.